Polycyclic Aromatic Hydrocarbons (PAHs) in seawater, marine sedimen and their accumulation in the Bombay-duck, Harpadon nehereus (Hamilton, 1822) of Tarakan waters - Ratno Achyani; Tri Prartono; Etty Riani (Jurnal Iktiologi Indonesia, 2015)
Polycyclic Aromatic Hydrocarbons (PAHs) are the most toxic pollutants among the hydrocarbon families and their existence in the marine environment are harmful to aquatic organisms and human because of their mutagenic and carcinogenic properties. The purpose of this study was to identify the component of PAHs and their concentration in the water, sediment and their accumulation in the muscle and liver of the Harpadon nehereus. Water and sediment samples were collected in the three locations and fish sample in one location surrounding the Tarakan Island in September 2010. All samples were extracted using a soxhlet apparatus, and injected to the gas chromatography-mass spectrometry (GC-MS Shimadzu QP2010, with a detection limit of 0.001 ppb) after being cleaned up for identification. Total PAH concentrations ranged from 6.36-380 ^g/l and 50-136 ng/g in the water and sediment, respectively. Total PAH concentrations in muscle and liver ranged from 605-1067 ng/g and -1679 ng/g, respectively. There was an indication that the Tarakan waters has been contaminated by PHAs which derived from coastal activities, and PHAs accumulated in the body of H. neherus. Abstrak Hidrokarbon aromatik polisiklik (PAH) merupakan bahan pencemar beracun dari kelompok hidrokarbon dan keberada-annya di lingkungan laut berbahaya bagi organisme akuatik dan manusia karena bersifat mutagenis dan karsinogenis. Penelitian ini bertujuan mengidentifikasi komponen PAH dalam air dan sedimen laut serta akumulasinya dalam daging dan hati ikan Horpodon neherus. Pengambilan sampel air dan sedimen dilakukan pada bulan September 2010 di tiga lo-kasi dan contoh ikan di satu lokasi di sekitar perairan Pulau Tarakan. Seluruh sampel diekstraksi dalam perangkat sox-hlet dan dianalisis dengan Kromatografi Gas-Spetrometri Massa (GC-MS) tipe Shimadzu QP2010 dengan detection limit sebesar 0,001 ppb. Konsentrasi total PAH dalam air dan sedimen berturut-turut berkisar antara 6,36-380 p.g/l dan 50-136 ng/g. Konsentrasi PAH total dalam daging dan hati ikan H. neherus berkisar antara 605-1067 ng/g dan 9771679 ng/g. Perairan Tarakan terindikasi telah terkontaminasi PAH yang diduga berasal dari kegiatan sekitar pulau Tara-kan dan PAH telah terakumulasi dalam tubuh ikan H. neherus.